Nitrogen Cycling Dynamics: Investigating Volatilization and its Interplay with N2 Fixation - Monib, Abdul Wahid; Niazi, Parwiz; Barai, Shah Mahmood; Sawicka, Barbara; Baseer, Abdul Qadeer; Nikpay, Amin; Fahmawi, Safa Mahmoud Saleem; Singh, Deepti; Alikhail, Mirwais; Thea, Berthin (Journal for Research in Applied Sciences and Biotechnology, 2024)
The nitrogen cycle is the biogeochemical cycle by which nitrogen is converted into multiple chemical forms as it circulates among atmospheric, terrestrial, and marine ecosystems, the conversion of nitrogen can be carried out through both biological and physical processes. Important processes in the nitrogen cycle include fixation, ammonification, nitrification, and denitrification. The majority of Earth's atmosphere (78%) is atmospheric nitrogen, making it the largest source of nitrogen. However, atmospheric nitrogen has limited availability for biological use, leading to a scarcity of usable nitrogen in many types of ecosystems. The nitrogen cycle is of particular interest to ecologists because nitrogen availability can affect the rate of key ecosystem processes, including primary production and decomposition. Human activities such as fossil fuel combustion, use of artificial nitrogen fertilizers, and release of nitrogen in wastewater have dramatically altered the global nitrogen cycle. Human modification of the global nitrogen cycle can negatively affect the natural environment system and also human health. Volatilization and its Relationship to N2 fascination in Nitrogen Cycle in agriculture field is discuss in this paper.